2-Azido-2-deoxy-3,4-O-isopropylidene-2-C-methyl-d-talono-1,5-lactone - Jenkinson, Sarah F. (International Union of Crystallography, 2010)
The relative stereochemistry of the title compound, C(10)H(15)N(3)O(5), was confirmed by the crystal structure determination. The absolute configuration was determined from the use of d-lyxonolactone as the starting material. The six-membered ring adopts a boat conformation with the larger azide group, rather than the methyl group, in the bowsprit position. In the crystal structure, a bifurcated intermolecular O—H⋯O/O—H⋯N hydrogen bond links molecules into chains running parallel to the b axis.